How to Write Persuasively Today. - Davis, Carolyn (ABC-CLIO, 2010)
Standard five-paragraph essays. Advertising copy. Opinion pieces, articles, sermons, and presentations. Persuasive written communication exists in many forms. And whether you are a student working on a paper, a professional with a business proposal, or a citizen looking to express ideas and views, at some point you must make your case with words. But what makes writing truly persuasive and memorable?